Wo hat sich das Endwort versteckt? – Auf der Suche nach dem Unlösbaren in der deutschen Amtssprache - Małgorzata Derecka (Linguistische Treffen in Wrocław, 2022)
Wars, catastrophes, pandemics, epidemics have always meant that man, instead of inventing problems for himself and complicating life, turned in his actions to the basic values of his earthly existence. These dramatic events and phenomena, which are inseparable from human history, seemed to “cleanse” the mind and bring thinking back on track with basic needs and fundamental, mostly positive feelings. The covid pandemic is such a turning point. However, the old concerns remain – including the question of political correctness in the use of language in German society. In this context, the article examines and analyses the guidelines for “Employees of the Berlin Administration on Diversity-Sensitive Language Use” published by the Berlin Senate in September 2020. The linguistically correct reorientation anchored in this document is intended to help the Berlin administration on its way to treating all citizens fairly. However, the German language seems to be a garden of traps in its grammatical structure. Critical voices are rising in society against the new regulations – not against the struggle for gender equality itself, but against the political proposals in language use, which seem to be getting closer and closer to the border of the absurd. In this context, this article attempts to present which difficulties and linguistic doubts arise from the new regulations on language use in Berlin’s authorities and offices. Old and new expressions are compared and the resulting problems of interpretation are discussed. Furthermore, various linguistic means of the form of expression to be corrected are discussed and examples are given. It will probably never be possible to find the final word that no longer hurts anyone and makes everyone in society equal. However, the struggle for social and societal equality must not be abandoned in these troubled times.